Exploring the feasibility of teaching Classical Chinese poetry: a learner-centred curriculum development for adult L2 learners of Chinese - Zhao, Yaqi (2017)
This dissertation highlighted the importance of learning classical Chinese poetry in L2 Chinese learners’ journey. Not only because the living tradition of Classical Chinese poetry, but also due to the significant role of Classical Chinese poetry in today’s Chinese culture and society Then the two questions was answered why CCP is teachable, and what to teach when teaching CCP through analysing the characteristics of CCP from its visual effects, authority effects, grammatical aspects, as well as its metaphor and symbolic meaning. This research found the current CCP courses in the universities worldwideand compared the advantages and disadvantages of them, aiming to support syllabus design for my CCP-focused trial session. A CCP introduction session was designed, implemented and evaluated step by step in this research. Pre-course survey was adopted in needs analysis. Pro-course survey and follow-up interview was employed in evaluation. Different from other traditional CCP class, my CCP trial session was learner-centred and organised by